THE SIGNIFICANCE OF BABUR’S SCIENTIFIC AND SPIRITUAL HERITAGE TODAY - Makhmudova, Khurmat Mukhtorovna (Innovative Development in Educational Activities, 2024)
This article tells about the life and work of Zakhiriddin Muhammad Babur, like all Timur princes, Babur studied military education, jurisprudence, Arabic and Persian languages under the tutelage of special teachers, great virtuous scholars, and read many historical and literary works, science - about his high interest in science and poetry, Amir Timur’s actions were aimed at capturing Samarkand, the capital of a state of strategic and geographical importance, and maintaining a strong state centered in Movarunnahr, as well as subjugating the northern part of India up to Bengal, carrying out major reforms in the field of social structure administration, The importance of his scientific and spiritual heritage today, the analysis of Babur’s works and works written about him, the importance of studying Babur’s legacy today, the need to know the past in order to think and think in a new way will be made